STRATEGIES FOR IMPROVING THE IDENTITY OF PESANTREN THROUGH INTERNATIONAL COOPERATION IN THE CONTEXT OF EDUCATIONAL DIPLOMACY - Amalia, Novi Rizka (Dauliyah Journal of Islamic and International Affairs, 2020)
In its implementation, an identity must be possessed by everyone to influence and attract other people and countries in this interdependent state / society. Pesantren is the oldest educational institution in Indonesia, the system is widely adopted by schools in general, especially in character education. The superiority of pesantren is to have an identity in developing an Islamic character, this is very much in accordance with the situation of Indonesia as a Muslim-majority country and a country based on Pancasila, namely the Almighty God as its first precept. In developing the identity of this pesantren, one strategy is needed to improve one of them by holding international cooperation as a reinforcement of the character and system in this educational institution. In this article the discussion focuses on cooperative strategies to strengthen the identity of Pesantren.